Transparency for results: testing a model of performance management in open government initiatives - Ingrams, Alex (2018)
Government transparency continues to challenge existing frameworks for understanding organizational performance. Transparency has proven difficult to measure and results assessing its impacts are mixed. This article sets forward a model of performance-based accountability in open government initiatives. Data come from the Open Government Partnership$1 (Bs (OGP) database of over 1,000 transparency initiatives across 50 countries in 2013. Ordered logistic regression estimates the effect of management practices on three different measures of transparency performance, and the results broadly support the model. Expert interviews from two country cases offer insight into how performance management is used in the context of transparency reforms. - Reproduced.s
Keywords: Transparency; Right to information; Citizen participation